Giving Booster Vaccinations to the Academic Community of the Faculty of Earth Science and Technology: Pemberian Vaksinasi Booster Pada Civitas Akademika Fakultas Ilmu dan Teknologi Kebumian - P. Parawansah; Juminten Saimin; S. Sukurni; La Rangki; Rahmawati Rahmawati; Nur Misa; Selvy Aulia (Yayasan Ahmar Cendekia Indonesia, 2022)
A booster vaccination is a COVID-19 vaccination after a person has received a complete primary dose of vaccination aimed at maintaining the level of immunity and extending the period of protection. The results of the study show that there has been a decrease in antibodies at six months after receiving a complete primary dose of COVID-19 vaccination, so that a follow-up or booster dose is needed to increase individual protection, especially in vulnerable groups of people. This Community Service activity was held on Monday, March 14, 2022 at 08.00 WITA at the Faculty of Earth Science and Technology (FITK) Halu Oleo University Kendari, which was attended by the Dean of the Faculty of Earth Science and Technology (FITK) Halu Oleo University, the Covid Vaccination Team -19 consisting of doctors, nurses and IT officers, and the Academic Community of the Faculty of Earth Science and Technology (FITK) as vaccination participants. The target of this Community Service activity is the Academic Community of the Faculty of Earth Science and Technology (FITK) at Halu Oleo Kendari University as many as 27 people, who were declared healthy and eligible to receive the Covid-19 vaccination after passing the registration and screening process from doctors. Abstrak Vaksinasi booster adalah vaksinasi COVID-19 setelah seseorang mendapat vaksinasi primer dosis lengkap yang ditujukan untuk mempertahankan tingkat kekebalan serta memperpanjang masa perlindungan. Hasil studi menunjukkan telah terjadi penurunan antibodi pada enam bulan setelah mendapatkan vaksinasi COVID-19 dosis primer lengkap, sehingga dibutuhkan pemberian dosis lanjutan atau booster untuk meningkatkan proteksi individu terutama pada kelompok masyarakat rentan. Kegiatan Pengabdian Kepada Masyarakat ini dilaksanakan pada hari senin, Tanggal 14 Maret 2022 Jam 08.00 Wita di Fakultas Ilmu dan Teknologi Kebumian (FITK) Universitas Halu Oleo Kendari, yang dihadiri oleh Dekan Fakultas Ilmu dan Teknologi Kebumian (FITK) Universitras Halu Oleo, Tim Vaksinasi Covid-19 yang terdiri dari dokter, perawat dan petugas IT, dan Civitas Akademika Fakultas Ilmu dan Teknologi Kebumian (FITK) sebagai peserta vaksinasi. Sasaran kegiatan Pengabdian Kepada Masyarakat ini adalah Civitas Akademika Fakultas Ilmu dan Teknologi Kebumian (FITK) dilingkup Universitas Halu Oleo Kendari sebanyak 27 orang, yang dinyatakan sehat dan layak untuk mendapatkan vaksinasi Covid-19 setelah melewati proses registrasi dan screening dari dokter.